PENGARUH SALINITAS TERHADAP PERKEMBANGAN STADIUM AKUATIK Aedes aegypti DI LABORATORIUM - Hotnida Sitorus; Wahyu Hidayat; Milana Salim; Marini Marini; Lasbudi Pertama Ambarita; Rika Mayasari (SPIRAKEL, 2021)
Aedes aegypti is known as the species of mosquito that breeds in fresh water, but due to the nature of adaptive this species found in habitats containing salt. This laboratory experiment aims to find out how different concentration of salinity will affect aquatic stages of Aedes aegypti. Salinity concentrations or treatment used in this study were 0‰, 2‰, 4‰, 6‰, 8‰ and 10‰ with five replicates. The observed parameters is the number of hatched eggs and number of surviving larvae or pupa after exposed to media containing salt. The results show that salinity influence both the number of hatced eggs and surviving larvae or pupae. There were decrease of number of hatched eggs and also the surviving larva or pupa as salinity increase. Analysis of variance showed significant relationship between salinity and the number of larvae or pupae survived but not with number of hatched eggs. Dengue vector adaptation against salinity become a phenomenon that needs to be examined and related to the spread of vector in habitats containing salt as well as transmission of the virus.